Pengaruh Struktur Modal, Profitabilitas, Dan Struktur Aset Terhadap Cash Flow Shock - Liana Anjelina; M Hendri Yan Nyale (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
To find out directly how capital structure, profitability and asset structure impact cash flow shocks in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange from 2020-2022. To understand the correlation between independent and dependent variables, this research uses quantitative methods. This study uses secondary data in the form of financial reports of food and beverage sector manufacturing companies listed on the IDX in the 2020-2022 period by applying a purposive sampling method. There are 20 companies that can meet the criteria, resulting in a sample size of 60 data. Research findings show that Cash Flow Shock is significantly and negatively influenced by capital structure variables. Meanwhile, Cash Flow Shock is influenced positively and significantly by profitability and asset structure. Keywords: Capital Structure, Profitability, Asset Structure, Cash Flow Shock